Associations between postprandial triglyceride concentrations and sex, age, and body mass index: cross-sectional analyses from the Tromsø study 2015–2016 - Mikkelsen, Mari; Wilsgaard, Tom; Grimsgaard, Sameline; Hopstock, Laila A.; Hansson, Patrik (Frontiers in Nutrition, 2023)
Introduction: Elevated serum triglyceride concentrations increase the risk of developing atherosclerosis, the leading cause of cardiovascular disease. Postprandial triglyceride concentrations have shown to be a stronger predictor of cardiovascular disease compared to fasting triglycerides. It is therefore clinically relevant to study patterns of postprandial triglyceride concentrations in a general adult population. Aims: The aim of this cross-sectional analysis was to examine postprandial triglyceride concentrations in women and men, and the association with age, body mass index and menopausal status. Methods: Non-fasting blood samples from 20 963 women and men aged 40 years and older, attending the seventh survey of the Tromsø Study (2015-2016), were analyzed for postprandial triglyceride concentrations using descriptive statistics and linear regression models. Self-reported time since last meal before blood sampling was categorized into one-hour intervals with 7+ hours considered fasting. Results: Men had higher triglyceride concentrations compared to women. The pattern of postprandial triglyceride concentrations differed between the sexes. In women, the highest triglyceride concentration (19 % higher compared to fasting level, p<0.001) was found 3-4 hours postprandially compared to 1-3 hours in men (30 % higher compared to fasting level, p<0.001). In women, all subgroups of age and BMI had higher triglyceride concentrations than the reference group (age 40-49 years and BMI<25 kg/m2), but no linear trend for age was observed. In men, triglyceride concentrations were inversely associated with age. Body mass index was positively associated with triglyceride concentration in both women (p<0.001) and men (p<0.001), although this association was somewhat modified by age in women. Postmenopausal women had significantly higher triglyceride concentrations compared to premenopausal women (p<0.05). Conclusions: Postprandial triglyceride concentrations differed in groups of sex, age, body mass index, and menopausal status.